Cosmic-ray fermion decay through tau-antitau emission with Lorentz violation - Escobar, C. A. (2018)
We study CPT and Lorentz violation in the tau-lepton sector of the Standard Model in the context of the Standard-Model Extension, parametrized by a coefficient which is thus far unbounded by experiment. We show that any nonzero value of this coefficient implies that, for sufficiently large energies, Standard Model fermions become unstable against decay due to the emission of a pair of tau-antitau leptons. We calculate the induced fermion energy-loss rate and we deduce the first limit on the Lorentz- and CPT-violation coefficient.